Status of PHELIX laser and first experiments - Neumayer, Paul; Kluge, Heinz-Jürgen (Laser and particle beams, 2005)
This paper reports on the status of the PHELIX petawatt laser which is built at the Gesellschaft fuer Schwerionenforschung (GSI) in close collaboration with the Lawrence Livermore National Laboratory (LLNL), and the Commissariat à l'Energie Atomique (CEA) in France. First experiments carried out with the chirped pulse amplification (CPA) front-end will also be briefly reviewed.
Gesehen am 03.03.2020